Maternal Perception of Her Child's Body Weight, Child Lifestyle Behavior Problems and Maternal Confidence in Managing These Behaviors - Flores-Peña, Yolanda (Curr Dev Nutr, 2020)
OBJECTIVES: To assess if child's lifestyle behavior problems (CLBP) and maternal confidence (MC) in managing these CLBP differ between mothers with accurate and inaccurate maternal perception of her child's body weight (MPCW). METHODS: A correlational study was conducted with 274 dyads (mother/preschool child) residents in Northeastern Mexico. Using a self-administered questionnaire, mothers answered: a) The Lifestyle Behavior Checklist, b) MPCW by word: I think my child is considered …underweight, normal weight, overweight or obese, 3) MPCW by image by selecting an image that represented their child's body weight. Child’ weight and height were measured. Descriptive statistics, Cramer's V, Mann-Whitney test, and ANOVA test were calculated. RESULTS: 25.2% of the children (n = 69) were overweight (OW) or obese (OB). Mothers of children were OW-OB had a lower MC than mothers of children with normal weight in CLBP: “eat too fast” (U = 5034, P = 0.001), “eat too much” (U = 5447, P = 0.004) and “eat unhealthy snacks/snacks” (U = 5471, P = 0.001). The CLBP that mothers of children were OW-OB have to manage include: “ eat very fast ”(F = 3.847, P = 0.050), “ discuss for food ”(F = 16.588, P = 0.001) and“ demand extra portions of food ”(F = 5.807, P = 0.017). Regarding the MPCW, 81.2% (n = 56) mothers of children were OW-OB and 18.5% (n = 32) mothers of children are normal weight had inaccurate MPCW by words (V = 355, P = 0.001), and 97.1% (n = 67) mothers of children were OW-OB and 63.0% (n = 109) mothers of children are normal weight had inaccurate MPCW by image (V = 235, P = 0.001). Mothers of OW-OB children with inaccurate MPCW had are more likely to perceived CLBP (Mean = 63.14, DE = 18.148) than those with accurate MPCW (Mean = 49.67, DE = 11,490) (F = 17,041, P = 0.001). CONCLUSIONS: The inaccurate MPCW can be an obstacle for the mother to recognize the CLBP that she has to manage. Interventions to promote accurate MPCE are recommended. FUNDING SOURCES: The Mexican National Council of Science and Technology.